2017
DOI: 10.1016/j.mcna.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Screening

Abstract: Lung cancer is the leading cause of cancer death in the United States. More than 80% of these deaths are attributed to tobacco use, and primary prevention can effectively reduce the cancer burden. The National Lung Screening Trial showed that low-dose computed tomography (LDCT) screening could reduce lung cancer mortality in high-risk patients by 20% compared with chest radiography. The US Preventive Services Task Force recommends annual LDCT screening for persons aged 55 to 80 years with a 30-pack-year smokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 65 publications
0
75
0
3
Order By: Relevance
“…Until recently, due to a lack of therapeutic targets for NSCLC, patients are usually diagnosed at an advanced stage of disease when they are illeligible to receive the standard treatment . Although there have been new therapeutic methods applied in clinical settings, the overall survival rate of NSCLC patients remains at 15% . Therefore, a better understanding of the underlying pathogenesis of NSCLC is urgently required in order to develop an effective therapeutic strategy to improve the survival rate of NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, due to a lack of therapeutic targets for NSCLC, patients are usually diagnosed at an advanced stage of disease when they are illeligible to receive the standard treatment . Although there have been new therapeutic methods applied in clinical settings, the overall survival rate of NSCLC patients remains at 15% . Therefore, a better understanding of the underlying pathogenesis of NSCLC is urgently required in order to develop an effective therapeutic strategy to improve the survival rate of NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is one of the most common cancers and the leading cause of cancer death in the world. 1,2 Due to poor diagnosis in the early stage, when symptoms are present, most lung cancer patients become aware of their malignancy only in the late stages, when surgical treatment is not preferable. 3,4 As a result, in order to improve the quality of life and extend survival, systemic chemotherapy is usually the final and main treatment for advanced lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, The National Lung Screening Trial (NLST) demonstrated the efficacy of LDCT scans in detecting lung cancer and reducing disease mortality rates by 20% (6). Since then, several scientific societies have modified their respective diagnostic guidelines to include LDCT screening for high risk patients, a test for which Medicare now reimburses patients (7). However, LDCT is an inefficient diagnostic tool.…”
Section: Review Articlementioning
confidence: 99%